Normativity and Beauty in Contemporary Arts - Tiziana Andina (Rivista di Estetica, 2017)
Our intuitions related to art are generally associated to ideas such as creativity, freedom of expression, experimentation. The fact that so many artists (especially writers, but also musicians, painters, performance artists) are or have been people with training in legal disciplines should be taken into account when considering the apparently extrinsic relationship between art and law. The question we have to answer is the following. When we make a judgment of taste looking, say, at the Mona Lisa, what does that mean exactly? What do we mean when we say that “the Mona Lisa is beautiful and an absolute masterpiece of Western art”? This statement contains a judgment of taste (Mona Lisa is beautiful) and an artistic judgment (it is a masterpiece of Western art). In what follows I will show that: i) the two judgments are different, ii) both judgments have normative nature, but the normativity of the judgment of taste refers to different elements from the artistic judgment and, finally, iii) contemporary visual arts require the formulation of an artistic judgment rather than a judgment of taste.